2020
DOI: 10.1186/s12905-020-01088-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and correlates of transactional sex among women of low socioeconomic status in Portland, OR

Abstract: Background Women who report transactional sex are at increased risk for HIV and other sexually transmitted infections (STIs). However, in the United States, social, behavioral, and trauma-related vulnerabilities associated with transactional sex are understudied and data on access to biomedical HIV prevention among women who report transactional sex are limited. Methods In 2016, we conducted a population-based, cross-sectional survey of women of low socioeconomic status recruited via respondent-driven sampli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…25 Finally, these behaviors are often congregated, as transactional sex is commonly reported among both PWUD and homeless individuals. 8,26,27 It is estimated that 2.9% to 3.8% of rural residents identify as sexual and gender minorities (SGMs) and may face increased STI risk. 28 In part, this is because rural SGMs (especially transgendered individuals) face substantial stigma and are less likely to use health care.…”
Section: Rural Sti Risk and Epidemiologymentioning
confidence: 99%
“…25 Finally, these behaviors are often congregated, as transactional sex is commonly reported among both PWUD and homeless individuals. 8,26,27 It is estimated that 2.9% to 3.8% of rural residents identify as sexual and gender minorities (SGMs) and may face increased STI risk. 28 In part, this is because rural SGMs (especially transgendered individuals) face substantial stigma and are less likely to use health care.…”
Section: Rural Sti Risk and Epidemiologymentioning
confidence: 99%
“…In a sample of people who used stimulants recruited through respondent-driven sampling in North Carolina [46], the majority (73%) reported at least one sexual behavior, and only 38% used condoms consistently, although sex risk factors were not associated with HIV prevalence. Polysubstance injecting (both opioids and methamphetamine) was associated with transactional and condomless sex among women of low socioeconomic status in Oregon [47]. The analysis of 2013–2017 case reporting of syphilis in the United States concluded that a substantial percentage of heterosexual syphilis transmission is occurring among persons who use drugs, particularly methamphetamine [48 ▪ ].…”
Section: Recent Findingsmentioning
confidence: 99%
“…As such, there may be an important opportunity to influence the trajectory of HIV in this population through increased uptake of state earned income tax credit laws, changes in the way the laws are implemented and increases in benefit generosity. Lastly, the HIV risk behaviors reflected in our composite HIV risk variable are implicated in a number of other infections that may have long-term health sequela such as pelvic inflammatory disease, cervical cancer and liver cancer [24]. Consequently, the long-term health and healthcare costs implications of more generous state earned income tax credit laws may be sizable.…”
Section: Discussionmentioning
confidence: 99%